Predictors of pregnancy stress and psychological birth trauma in women undergoing vaginal delivery: a cross-sectional study in China - Dongmei Ma; Shiwen Sun; Jialu Qian; Man Wang; Huimin Gu; Jingjing Lou; Xiaoyan Yu (BMC, 2023)
Abstract Background Psychological birth trauma exhibits a high incidence worldwide, resulting in a wide range of negative impacts on mothers, infants, couples, families and society at large through the maternal-centered ripple effect. However, there is currently limited research on psychological birth trauma in China. Social support and pregnancy stress are important influencing factors of psychological birth trauma. Consequently, this study aimed to explore predictors of pregnancy stress and psychological birth trauma in women undergoing vaginal delivery in China. Methods This cross-sectional study was performed at a single medical center between December 2021 and May 2022 in Hangzhou, China. Participants were selected using a convenience sampling technique. A total of 351 postpartum women within one week after vaginal delivery were included. Questionnaires were used to collect sociodemographic and obstetric characteristics and scores on the Pregnancy Stress Rating Scale (PSRS), City Birth Trauma Scale (City BiTS), Social Support Rating Scale (SSRS) and Family Adaptation Partnership Growth Affection and Resolve index (Family APGAR). Both univariate analysis and multiple linear regression analysis were conducted to assess predictors of pregnancy stress and psychological birth trauma. Results The median (IQR) of PSRS and City BiTS scores were 10.00 (14.00) and 3.00 (9.00), respectively. The incidence of postpartum posttraumatic stress disorder was 4.0% (14/351). Parity, social support, family support and level of education were predictors of pregnancy stress. Delivery complications, psychological traumatic event, pregnancy stress and family support were predictors of psychological birth trauma (P < 0.05). Conclusion Pregnancy stress is related to social support, family support and some sociodemographic and obstetric characteristics. Psychological birth trauma is correlated with delivery complications, psychological traumatic event, pregnancy stress and family support. Consequently, enhancing social support, especially family support, for pregnant women as a means of reducing pregnancy stress can effectively prevent psychological birth trauma.